2007
DOI: 10.1111/j.1750-3841.2007.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality Changes during Refrigerated Storage of MA‐Packaged Pre‐rigor Fillets of Farmed Atlantic Cod (Gadus morhua L.) Using Traditional MAP, CO2 Emitter, and Vacuum

Abstract: Quality changes during 3 wk of refrigerated storage (1.3 degrees C) were studied on pre-rigor filleted farmed Atlantic cod packed in modified atmosphere (MAP, 60% CO2 and 40% O2) or vacuum. The packages of MAP contained either a CO2 emitter and low gas volume to product volume (g/p ratio) of 1.3, or a 3.9 g/p ratio and no emitter. The CO2 level remained stable or increased in the packages with CO2 emitter, whereas the CO2 level in the packages with no CO2 emitter decreased to 40% after 4 d of refrigerated stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
91
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(114 citation statements)
references
References 33 publications
22
91
0
1
Order By: Relevance
“…A liquid absorbent pad (SuperCore mP-2500, McAirlaid's, Steinfurt, Germany) was placed in the bottom of half of the packages while a CO 2 emitting pad was placed in the rest. The CO 2 emitters were prepared (at Nofima, Ås, Norway) by adding 0.304 g NaHCO 3 and 0.237 g citric acid to a liquid absorber pad (Absorbent Pad Dri-Loc, Friedrichsdorf, Germany) based on prior experiment (Hansen et al, 2007). Similar CO 2 emitter was used for both vacuum packages and MAP.…”
Section: Packaging Methods Materials and Storagementioning
confidence: 99%
See 1 more Smart Citation
“…A liquid absorbent pad (SuperCore mP-2500, McAirlaid's, Steinfurt, Germany) was placed in the bottom of half of the packages while a CO 2 emitting pad was placed in the rest. The CO 2 emitters were prepared (at Nofima, Ås, Norway) by adding 0.304 g NaHCO 3 and 0.237 g citric acid to a liquid absorber pad (Absorbent Pad Dri-Loc, Friedrichsdorf, Germany) based on prior experiment (Hansen et al, 2007). Similar CO 2 emitter was used for both vacuum packages and MAP.…”
Section: Packaging Methods Materials and Storagementioning
confidence: 99%
“…On the other hand, an increased g/p ratio in a package of modified atmosphere can be compensated by use of a CO 2 emitter, which develops CO 2 gas after sealing the package. Studies performed on fillets from farmed Atlantic cod and Atlantic salmon have shown that a CO 2 emitter can compensate for a g/p ratio of 4/1 and 3/1, respectively (Hansen, Mørkøre, Rudi, Olsen & Eie, 2007;Hansen, Mørkøre, Rudi, Rødbotten et al, 2009). The CO 2 emitter additionally functions as a liquid absorbent pad, and it enables low g/p ratios without packaging collapse.…”
Section: Introductionmentioning
confidence: 98%
“…Na presença de CO 2 , o desenvolvimento de Shewanella putrefaciens e de Pseudomonas é inibido, sendo o Photobacterium phosphoreum o principal responsável pela degradação de filé de bacalhau numa atmosfera rica em CO 2 , em ambiente refrigerado. O P. phosphoreum existe no meio marinho e revelou um desenvolvimento elevado em condições de anaerobiose e uma elevada resistência ao CO 2 , sendo, por isso, o organismo responsável pela degradação da maioria do pescado MP embalado em atmosfera modificada (HANSEN et al, 2007; ÓLAFSDÓTTIR et al, 1 9 9 7 ; D A L G A A R D e t a l . , 1 9 9 3 ) .…”
Section: Pescado Minimamente Processado Em Mapunclassified
“…CO 2 and MAP (modified atmosphere packaging) reduces the growth of Shewanella and Pseudomonas [25][26][27][28]. Using CO 2 alone would cause it to dissolve in meat and fish resulting in package shrinking and deformation [29][30].…”
Section: Introductionmentioning
confidence: 99%
“…A disadvantage of MAP is that the increased package volume would increase transportation costs [25]. With vacuum packaging, there is less volume but it is less effective than MAP [26].…”
Section: Introductionmentioning
confidence: 99%